Capturing innovation in surgeries: an evaluation from a management perspective. (19th July 2019) - Olcay, Gökçen Arkalı; Narcı, Hacer Özgen; Gürler, Metin; Bulu, Melih
Surgery is considered as an integral part of any health system, comprising 30% of global burden of disease along with serious access problems and catastrophic payments across the world. More than 230 million major surgeries are done every year. Surgical innovations typically represent the greatest part of innovations in terms of their contributions to ensuring safer and high-quality care and thus saving lives in the field of healthcare management. Such innovations also contribute significantly to the knowledge society. Correctly identifying innovations in surgery and enabling them to be known and adapted by other surgeons is a critical concern for all stakeholders in healthcare. There exists no information on surgical innovations from a managerial perspective in Turkey. This study aims to explore how surgeons identify surgical innovations based on their real experiences of past surgeries using a semi-structured questionnaire distributed to surgeons in a major hospital chain in &#İstanbul, Turkey. The results shed light on recognising and evaluating surgical innovations provided by the practicing surgeons via a management perspective.